Numeric Analysis Method of Fluid-Solid Coupling Vibration in Train Passing by Each Other at High Speed - CUI Tao; ZHANG Wei-hua; WANG Yan (机车电传动)
In order to study safety of train passing by each other with consideration of fluid-solid coupling friendship and avoid the large damage to structure and running safety from the interaction of train and air, a new numerical analysis method of fluid-solid coupling vibration was advanced by integrating the finite volume method of computational fluid dynamics and numerical simulation method of multi-body systems dynamics, with which the flow field equations and dynamics equations of multi-body systems were solved. Safeties of trains passing by each other at speed of 350 km/h were analyzed by fluid-solid coupling method and traditional separation method respectively and compared to line test, which showed that fluid-solid coupling method was valid. And with difference analysis of the two methods, the coupling method was proved safer.